Management of islamic education based on religious culture - M Sahrawi Saimima (12 Waiheru, 2022)
Management is a process of activities that includes four functions including planning, organizingn, implementing and controlling. In its implementation, the management of Islamic education based on religious culture has an urgent role in directing humans to worship Allah and be on good terms with fellow human beings. This study aims to find out what religious value bases are often applied in Educational Institutions, and how religious culture management is applied. To facilitate the course of this research, researchers used a literature research method with descriptive data analysis techniques in 15 research articles on Religious Culture published from various educational journals with a time span from 2017 to 2022. The results of the study showed that the religious cultural base applied used the values of Tawhid, Akhlak, Amanah and Social. In addition, in the stages of its management, the aspects contained within the religious culture must be applied systematically and scheduled.